2012
DOI: 10.1016/j.foodres.2012.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of coffee antioxidants: Impact of brewing time and method

Abstract: The aim of this work was to study the extraction behavior of the main coffee antioxidants (caffeoylquinic acids, melanoidins and caffeine) and the antioxidant capacity, during brewing time in the most widely consumed coffee brew methods (filter and espresso) in coffee. Antioxidant capacity by colorimetric assays (Folin-Ciocalteau, ABTS and DPPH) and electron spin resonance spectroscopy techniques (Fremy's salt and TEMPO) were analyzed. In espresso coffee, more than 70% of the antioxidants (except dicaffeoylqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
130
5
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(178 citation statements)
references
References 42 publications
28
130
5
3
Order By: Relevance
“…Therefore, the release of diCQAs bound to melanoidins is rather difficult to that of monoCQAs. However, as proposed by Ludwig et al, 32 the use of an extraction system with turbulences during few minutes facilitates the contact of grounds and water, a polar solvent, and favors the caffeoylquinic acids extraction, also diCQAs.…”
Section: Caffeoylquinic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the release of diCQAs bound to melanoidins is rather difficult to that of monoCQAs. However, as proposed by Ludwig et al, 32 the use of an extraction system with turbulences during few minutes facilitates the contact of grounds and water, a polar solvent, and favors the caffeoylquinic acids extraction, also diCQAs.…”
Section: Caffeoylquinic Acidsmentioning
confidence: 99%
“…Similar behaviour was also observed in coffee brews by other authors. 12,32,47 For that reason, all TEMPO results should be considered as very low, including the significantly higher TEMPO antioxidant capacity of the aqueous extracts obtained from Arabica spent coffee grounds from filter coffeemaker. This higher result might be explained by the slightly higher browning index (Abs 420nm 0.165), but also because melanoidins have different antioxidant capacities, depending on the structure, their composition and the phenolics bound in their skeleton.…”
Section: Antioxidant Capacity Of Spent Coffeementioning
confidence: 99%
“…The presence of (poly)phenolic compounds, mainly chlorogenic acids, and other major coffee compounds, such as caffeine and melanoidins, and their contribution to the antioxidant capacity of coffee have been widely studied during last decades (Crozier, Jaganath & Clifford, 2009; Delgado-Andrade, Rufian-Henares & Morales, 2005;Ludwig, Sanchez, Caemmerer, Kroh, de Peña & Cid, 2012). However, coffee contains many other minor compounds, such as volatile compounds, that might play a role in the antioxidant capacity of coffee.…”
Section: Introductionmentioning
confidence: 99%
“…The roasting method might also play an important role in the CGA content of the final coffee product. In fact, in the only article available on the CGA concentration in espresso coffee, it is reported that the CGA content is higher in Arabica rather than in Robusta EC samples (Ludwig et al, 2012). Various analytical methods have been proposed for the quantification of chlorogenic acids in coffee: HPLC (High-performance liquid chromatography) is the most common method, coupled with UV detector (Bicchi, Binello, Pellegrino, & Vanni, 1995;Fujioka & Shibamoto, 2008;Ky, Noirot, & Hamon, 1997; or with a mass spectrometer (Blumberg, Frank, & Hofmann, 2010).…”
Section: Introductionmentioning
confidence: 99%